2018
DOI: 10.3233/jnd-180310
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Psychopathology Features, Personality, and Coping in Myotonic Dystrophy Type 1

Abstract: Background:The last literature review on psychopathological features in Myotonic Dystrophy type 1 had been conducted by Ambrosini and Nurnberg in 1979. Since that date, many researches had been carried out.Objective:The aim of this study is (i) to systematically obtain and evaluate the relevant literature on psychopathological features, personality, and coping in individuals with adult phenotypes of Myotonic Dystrophy type 1. (ii) To summarize current research findings and draw conclusions for future research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 66 publications
2
20
0
1
Order By: Relevance
“…Adult DM patients develop various neuropsychological symptoms including excessive daytime sleepiness, cognitive decline, depression, apathy and avoidant personality (Thornton, 2014; Minier et al, 2018). Similar to DM1, the CNS symptoms in DM2 are common but less severe.…”
Section: Introductionmentioning
confidence: 99%
“…Adult DM patients develop various neuropsychological symptoms including excessive daytime sleepiness, cognitive decline, depression, apathy and avoidant personality (Thornton, 2014; Minier et al, 2018). Similar to DM1, the CNS symptoms in DM2 are common but less severe.…”
Section: Introductionmentioning
confidence: 99%
“…These cognitive deficits are also observed in DM1 (123). Brain insulin signaling is also linked to affective state, disturbances of which may be involved in depressive symptoms observed in DM1 (124, 125). Obsessive-compulsive disorder (OCD) personality traits are also a feature of DM1 (125).…”
Section: Clinical Evidence Of Insulin Signaling Involvement In Dm1mentioning
confidence: 99%
“…Brain insulin signaling is also linked to affective state, disturbances of which may be involved in depressive symptoms observed in DM1 (124, 125). Obsessive-compulsive disorder (OCD) personality traits are also a feature of DM1 (125). We have established that in OCD cohorts, alterations in insulin signaling occur (126), and that increased insulin resistance is associated with decreased behavioral flexibility (127).…”
Section: Clinical Evidence Of Insulin Signaling Involvement In Dm1mentioning
confidence: 99%
“…Minier et al [49] conducted a systematic literature review of psychopathological features in DM1 and reported that patients with DM1 present mild psychopathological problems, such as interpersonal difficulties, lack of interest, dysphoria, concern about bodily functioning, and hypersensibility. However, they do not present more psychiatric disorders than the general population, except for personality disorders and depression.…”
Section: Psychopathological Features and Personality Of Dm1 Patientsmentioning
confidence: 99%